CROP ALERT: A Citrus Canker Fact Sheet for Homeowners - H. L. Chamberlain; Pamela D. Roberts; Lavern W. Timmer; Kuang-Ren Chung; Mongi Zekri (EDIS, 2003)
Citrus canker (CC) is caused by the bacterial pathogen Xanthomonas axonopodis pv. citri. The pathogen enters host tissues through wounds and natural openings called stomata. It is a serious disease of all citrus and some citrus relatives. This document is PP194, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Insitute of Food and Agricultural Sciences, University of Florida. Original Publication Date: September 2001. Reviewed: June 2003.